Molybdenum carbide / nitrogen-doped carbon composite material and preparation method and application thereof

By using molybdenum carbide/nitrogen doped carbon composite materials as functional additives in the positive electrode of lithium sulfur batteries, the problem of slow conversion kinetics of lithium polysulfide in lithium sulfur batteries is solved, and the capacity and cycle stability of the battery are significantly improved.

CN119542389AActive Publication Date: 2025-02-28HEFEI UNIV OF TECH

Patent Information

Application Number
CN202411708970.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

In terms of performance improvement and commercialization, lithium sulfur batteries face the problems of insulator properties of sulfur and its discharge product lithium sulfide, which leads to slow redox kinetics of the battery, low utilization of active sulfur, and slow conversion kinetics of lithium polysulfide, leading to capacity attenuation and Coulomb efficiency reduction.

Method used

The composite material is prepared by hydrothermal and high-temperature calcining methods by using molybdenum carbide/nitrogen doped carbon composite material as a functional additive for the positive electrode of lithium sulfur battery, and the chemical adsorption and reversible conversion of lithium polysulfide are used to promote the chemical adsorption and reversible conversion of lithium polysulfide.

Benefits of technology

It significantly improves the capacity, cycle stability and rate performance of lithium-sulfur batteries, effectively inhibits the dissolution and shuttle of polysulfides, and improves the utilization rate of active substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542389A_ABST
    Figure CN119542389A_ABST
Patent Text Reader

Abstract

The invention discloses a molybdenum carbide / nitrogen-doped carbon composite material and a preparation method and application thereof, and belongs to the technical field of new energy materials and devices. The preparation method comprises the following steps: uniformly mixing ammonium molybdate, glucose and g-C3N4, and carrying out hydrothermal and high-temperature calcination treatment to obtain a composite material (Mo2C / NC) in which a nano Mo2C electrocatalyst is dispersed and distributed on a nitrogen-doped carbon matrix. The nitrogen-doped carbon in the composite material has a hierarchical porous structure, so that the electrolyte permeation and ion transmission capabilities are enhanced; the nitrogen-doped active sites not only enhance the adsorption performance of the porous carbon on polysulfide, but also improve the catalytic activity by optimizing the coordination structure of Mo2C; mo2C can chemically adsorb and efficiently catalyze reversible conversion of polysulfide, and the utilization rate of active substances is increased. When the composite material is used as a positive electrode additive of a lithium-sulfur battery, dissolution and shuttling of polysulfide can be effectively inhibited, so that the battery has high specific capacity, rate capability and excellent cycle reversibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials and devices, and specifically relates to a molybdenum carbide / nitrogen-doped carbon composite material and a preparation method and application thereof. Background Art

[0002] Against the backdrop of the growing global energy crisis and increasing environmental awareness, breakthroughs in electrochemical energy storage technology have become the key to promoting efficient, clean and sustainable energy development. Among the many new electrochemical energy storage technologies, lithium-sulfur (Li-S) batteries based on the multi-step multi-electron reversible oxidation-reduction reaction of elemental sulfur have a high theoretical specific capacity (1675 mAh g -1 ), abundant sulfur resources and good environmental friendliness, and is regarded as one of the most promising candidates for the next generation of electrochemical energy storage systems.

[0003] However, Li-S batteries still face the following major bottlenecks in terms of performance improvement and commercialization: (1) Sulfur and its discharge product lithium sulfide (Li2S) are both insulators of electrons and lithium ions, resulting in slow battery redox kinetics and low utilization of active sulfur; (2) The intermediate lithium polysulfides (LiPSs) produced during the charge and discharge process will lead to the "shuttle effect", which not only causes the continuous loss of active materials during the cycle, but also accelerates capacity decay and coulombic efficiency reduction due to the slow conversion kinetics of LiPSs; (3) The volume change of sulfur during the charge and discharge process is significant, which easily causes the active materials to fall off the current collector, further affecting the structural stability of the battery. Therefore, exploring effective strategies to regulate the conversion of LiPSs and inhibit the shuttle effect is crucial to improving the stability and performance of Li-S batteries.

[0004] To solve these problems, researchers have tried a variety of strategies, such as designing composite conductive sulfur carriers, optimizing electrolytes, and functional separators / interlayers to inhibit the dissolution shuttle of LiPSs and accelerate the reversible transformation of LiPSs. Among the many candidate sulfur-carrying materials, porous carbon materials are considered to be ideal sulfur carrier materials due to their high conductivity, excellent specific surface area and structural stability. However, due to the lack of polar active sites, they have weak adsorption capacity for LiPSs and limited effect in catalytic conversion. In contrast, although polar metal compounds have good adsorption capacity for LiPSs, their conductivity is usually poor, which easily saturates the adsorption sites and is not conducive to the rapid conversion of LiPSs. Studies have shown that the electrochemical performance of Li-S batteries can be significantly improved by introducing polar catalytic materials into porous carbon. Among them, metal carbides (such as molybdenum carbide) can effectively promote the catalytic conversion of LiPSs due to their excellent conductivity, high chemical adsorption performance and catalytic activity, thereby significantly enhancing the electrochemical reaction activity and the overall performance of Li-S batteries. Summary of the invention

[0005] The present invention aims to address the deficiencies of existing lithium-sulfur battery cathode materials and their preparation technologies, and to provide a molybdenum carbide / nitrogen-doped carbon composite material and its preparation method and application. The composite material can be used as a functional additive for the cathode of a lithium-sulfur battery, and has excellent electrical conductivity and efficient chemical adsorption and catalytic conversion of lithium polysulfide, thereby significantly improving the capacity, cycle stability and rate performance of lithium-sulfur batteries.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The present invention provides a molybdenum carbide / nitrogen-doped carbon composite material, in which fine Mo2C nanoparticles are uniformly dispersed in a nitrogen-doped carbon matrix.

[0008] The present invention provides a method for preparing a molybdenum carbide / nitrogen-doped carbon composite material, wherein g-C3N4 is used as a template, ammonium molybdate ((NH4)2MoO4·4H2O) is used as a molybdenum source, and glucose (C6H 12 O6) as a carbon source, which are uniformly mixed and then hydrothermally and high-temperature calcined to obtain a molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC).

[0009] As a preferred technical solution of the present invention, the specific steps of the preparation method are as follows:

[0010] (1) placing 20-25 g of urea in a tubular furnace for high-temperature calcination to obtain g-C3N4, wherein the calcination atmosphere is air, the temperature is 520-560°C, the holding time is 3-4 h, and the heating rate is 3-5°C / min;

[0011] (2) At room temperature, 0.1-0.2 g (NH4)2MoO4·4H2O and 0.4-0.6 g C6H 12 O6 was dissolved in 20 mL of deionized water, and 0.1-0.2 g of g-C3N4 was ultrasonically dispersed in the solution and stirred for 8-12 h to obtain a milky white solution;

[0012] (3) placing the mixed solution obtained in step (2) in a reaction vessel for hydrothermal reaction at a temperature of 120 to 150° C. for 8 to 12 hours; then filtering the reaction product and drying it for later use;

[0013] (4) placing the product obtained in step (3) in an inert atmosphere for high-temperature calcination treatment, wherein the calcination atmosphere is argon, the temperature is 800-850° C., the holding time is 2-3 h, and the heating rate is 2-4° C. / min, to obtain Mo2C / NC;

[0014] (5) The Mo2C / NC prepared in step (4) is fully ground and mixed with Ketjen black (KB) in a certain proportion to obtain a conductive carrier (KB / Mo2C / NC), wherein the mass ratio of Mo2C / NC is 2% to 8%; the conductive carrier is composited with active sulfur by a melt sulfurization process to obtain a composite sulfur positive electrode material (KB / Mo2C / NC-S) for a lithium-sulfur battery.

[0015] The present invention also proposes the application of the molybdenum carbide / nitrogen-doped carbon composite material in the positive electrode material of lithium-sulfur batteries. The composite sulfur positive electrode material (KB / Mo2C / NC-S) for lithium-sulfur batteries prepared by the molybdenum carbide / nitrogen-doped carbon composite material, the conductive agent, and the binder are fully ground and mixed in a mass ratio of 8:1:1 to obtain a slurry. The obtained slurry is evenly coated on aluminum foil, vacuum dried at 70°C for 24 hours and cut to obtain a lithium-sulfur battery positive electrode sheet, wherein the active sulfur area loading is 1.5-2.0 mg / cm 2 Among them, molybdenum carbide / nitrogen-doped carbon composite material, as a functional additive for the positive electrode of lithium-sulfur batteries, can effectively improve the utilization rate of active sulfur.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0017] The present invention uses the prepared molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC) as a functional additive for the positive electrode of a lithium-sulfur battery, and after mixing with Ketjen black (KB), uses it as a conductive carrier of active sulfur (KB / Mo2C / NC) and melts and composites it with sulfur to obtain a composite positive electrode material (KB / Mo2C / NC-S) for a lithium-sulfur battery. Among them, the nano Mo2C electrocatalyst is dispersed in the nitrogen-doped carbon matrix. The nitrogen-doped carbon has a hierarchical porous structure, which enhances the electrolyte penetration and ion transmission capabilities; the nitrogen-doped active site not only enhances the adsorption performance of the porous carbon to polysulfides, but also can improve its catalytic activity by optimizing the coordination structure of Mo2C; Mo2C can chemically adsorb and efficiently catalyze the reversible transformation of polysulfides, thereby improving the utilization rate of active substances. The composite material is used as a functional additive for the positive electrode of a lithium-sulfur battery, which can effectively inhibit the dissolution and shuttle of polysulfides, and significantly improve the capacity, rate performance and cycle life of the battery.

[0018] In addition, the preparation process of this composite material is simple, easy to control, and has a high yield, which is conducive to industrial promotion and has opened up a new path for the preparation of positive electrode additive materials for lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the XRD curve of g-C3N4 in Example 1.

[0020] Figure 2 This is the XRD curve of the molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC) in Example 1.

[0021] Figure 3 This is the SEM morphology of g-C3N4 in Example 1.

[0022] Figure 4 This is the SEM morphology of the molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC) in Example 1.

[0023] Figure 5 (a) TEM and (b) HRTEM morphology images of the molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC) in Example 1.

[0024] Figure 6 (a) N2 adsorption-desorption isotherm and (b) DFT pore size distribution diagram of the molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC) in Example 1 (the inset is a curve diagram of the pore size distribution ≤ 2 nm).

[0025] Figure 7 The XPS full spectrum (a) of the molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC) in Example 1 and the XPS high-resolution spectra of C1s (b), Mo3d (c), and N 1s (d) elements.

[0026] Figure 8 This is the thermogravimetric analysis of the molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC) in Example 1.

[0027] Fig. 9 The constant current charge and discharge cycle test results of the lithium-sulfur batteries prepared in Example 1 and Comparative Example 1 at a rate of 0.5C.

[0028] Fig.10 The performance test results of the lithium-sulfur batteries prepared in Example 1 and Comparative Example 1 at different rates. DETAILED DESCRIPTION

[0029] The molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC) provided by the present invention and its preparation method and application are further described in detail below in conjunction with the embodiments and drawings.

[0030] Example 1

[0031] This example provides a molybdenum carbide / nitrogen-doped carbon composite material, which uses g-C3N4 as a template, ammonium molybdate ((NH4)2MoO4·4H2O) as a molybdenum source, and glucose (C6H 12 O6) as the carbon source, and then evenly mix them and perform hydrothermal and high-temperature calcination to obtain a molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC). The specific steps are as follows:

[0032] (1) 20 g of urea was placed in a tubular furnace for high-temperature calcination to obtain g-C3N4, wherein the calcination atmosphere was air, the temperature was 550°C, the insulation time was 4 h, and the heating rate was 5°C / min.

[0033] (2) At room temperature, 0.12 g (NH4)2MoO4·4H2O and 0.5 g C6H 12 O6 was dissolved in 20 mL of deionized water, and 0.13 g of g-C3N4 was weighed and ultrasonically dispersed in the solution and stirred for 8 h to obtain a milky white solution.

[0034] (3) The mixed solution obtained in step (2) was placed in a reactor for hydrothermal reaction at a temperature of 120° C. for 10 h; the reaction product was then filtered and dried for later use.

[0035] (4) placing the product obtained in step (3) in an inert atmosphere for high-temperature calcination, wherein the calcination atmosphere is argon, the temperature is 800° C., the holding time is 3 h, and the heating rate is 2° C. / min, to obtain Mo2C / NC.

[0036] (5) The Mo2C / NC prepared in step (4) is fully ground and mixed with Ketjen black (KB) in a certain ratio to obtain a conductive carrier (KB / Mo2C / NC), wherein the mass ratio of Mo2C / NC is 3%. The conductive carrier is composited with active sulfur by a melt sulfurization process to obtain a composite sulfur positive electrode material for a lithium-sulfur battery (KB / Mo2C / NC-S).

[0037] The molybdenum carbide / nitrogen-doped carbon composite material is used in the positive electrode material of lithium-sulfur batteries. KB / Mo2C / NC-S, conductive agent Super P, and binder polyvinylidene fluoride PVDF are fully ground and mixed in a mass ratio of 8:1:1 to obtain a slurry. The obtained slurry is evenly coated on aluminum foil, vacuum dried at 70°C for 24 hours and cut to obtain a lithium-sulfur battery positive electrode sheet, in which the active sulfur area loading is 1.6 mg / cm 2 .

[0038] See also Figure 1 , which is the XRD curve of g-C3N4 prepared in this example. Figure 3 It can be seen that the carbon matrix presents a wrinkled sheet-like disordered stacking structure, which can greatly increase the specific surface area of ​​the composite material, which is beneficial to enhance the adsorption performance of the carbon matrix for polysulfides, and at the same time can enhance the infiltration and penetration of the electrolyte.

[0039] See also Figure 2 , This figure shows the XRD curve of molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC). Figure 4 and Figure 5It can be seen that the tiny Mo2C nanoparticles are dispersed in the nitrogen-doped carbon matrix, and Mo2C can chemically adsorb and efficiently catalyze the reversible transformation of polysulfides, enhance the electrochemical reaction kinetics and improve the utilization rate of active materials. Figure 6 It can be seen that the specific surface area of ​​this composite material is 184.82m 2 / g, and the high specific surface area can provide abundant adsorption and catalytic polysulfide reaction sites.

[0040] See also Figure 7 , This figure shows the XPS full spectrum (a) and XPS high-resolution spectra of C1s (b), Mo 3d (c), and N 1s (d) of molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC). Mo2C / NC composite material contains four elements: C, N, O, and Mo ( Figure 7 a), where the O element mainly comes from the sample's adsorption of moisture in the air and surface oxidation. In the high-resolution spectrum of C1s ( Figure 7 b) There are three features: C-Mo bond (285.0 eV), CC / C=C bond (284.2 eV), CN bond (287.5 eV); in the high-resolution spectrum of Mo 3d ( Figure 7 c) There are six characteristic peaks: the characteristic peaks at 227.8eV and 230.9eV correspond to Mo 2+ 3d 5 / 2 and Mo 2+ 3d 3 / 2 The peaks at 228.9 eV and 233.3 eV correspond to Mo 4+ 3d 5 / 2 and Mo 4+ 3d 3 / 2 ; The peaks at 231.8eV and 235.6eV correspond to Mo 6+ 3d 5 / 2 and Mo 6+ 3d 3 / 2 The binding energy of Mo 6+ and Mo 4+ This is due to the surface oxidation of Mo2C; in the high-resolution spectrum of N1s ( Figure 7 d) There are three characteristic peaks: pyridine-N bond (397.2 eV), graphite-N bond (400.4 eV) and Mo 3p 3 / 2 (393.6eV). XPS test results show that there are bonds between molybdenum, nitrogen and carbon in the molybdenum carbide / nitrogen-doped carbon composite (Mo2C / NC). Nitrogen-doped active sites not only enhance the adsorption performance of porous carbon for polysulfides, but also improve its catalytic activity by optimizing the coordination structure of Mo2C.

[0041] See also Figure 8This figure shows the thermogravimetric analysis curve of molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC), the temperature range is 0-700℃, and the atmosphere is air. At about 150℃, Mo2C is oxidized to MoO3, and at about 350℃, the carbon material burns and disappears in the air. The content of Mo2C is calculated to be 34wt%.

[0042] The KB / Mo2C / NC conductive carrier prepared in this example was melt-compounded with active sulfur as the positive electrode material, and the lithium sheet was used as the negative electrode; Celgard 2500 polypropylene film was used as the separator; lithium bis(trifluoromethylsulfonic acid)imide (LiTFSI) was used as the solute, and 1,3-dioxolane DOL and ethylene glycol dimethyl ether DME with a volume ratio of 1:1 were used as the solvent, and the concentration was 1 mol·L -1 solution and added 1wt% LiNO3 as electrolyte; finally, 2032 button lithium sulfur batteries were assembled and charge and discharge tests were carried out, and the test voltage window was 1.7-2.8V.

[0043] Comparative Example 1

[0044] In order to compare and illustrate the effect of the Mo2C / NC positive electrode additive for lithium-sulfur batteries provided by the present invention on the electrochemical performance of lithium-sulfur batteries, the preparation of the lithium-sulfur battery in this comparative example 1 is basically the same as that in Example 1, except that the battery is assembled with a positive electrode material without adding Mo2C / NC and a charge and discharge test is performed.

[0045] The KB / S electrode material prepared in this comparative example was used as the working electrode, the lithium sheet was used as the counter electrode, the Celgard 2500 polypropylene film was used as the diaphragm, lithium bis(trifluoromethylsulfonate)imide (LiTFSI) was used as the solute, and 1,3-dioxolane DOL and ethylene glycol dimethyl ether DME in a volume ratio of 1:1 were used as the solvent, and the concentration was 1 mol·L -1 solution and added 1wt% LiNO3 as electrolyte; finally, 2032 button lithium sulfur batteries were assembled and charge and discharge tests were carried out, and the test voltage window was 1.7-2.8V.

[0046] See also Fig. 9, this figure shows the constant current charge and discharge cycle test results of the lithium-sulfur batteries prepared in Example 1 and Comparative Example 1 at a rate of 0.5C. As shown in the figure, when the current density is 0.5C, the initial discharge capacity of the lithium-sulfur battery assembled in Example 1 is 978.9mAh / g, and the reversible capacity remains at 632.5mAh / g after 500 cycles. The decay rate per cycle is about 0.071%, and the capacity retention rate is 64.6%, showing good cycle stability. The lithium-sulfur battery assembled in Comparative Example 1 has an initial discharge capacity of 822.3mAh / g at 0.5C. After 500 cycles, the capacity drops to 334.1mAh / g, the capacity retention rate is only 40.6%, and the average capacity decay rate per cycle is 0.12%. Compared with Comparative Example 1, the positive electrode material in Example 1 is significantly improved in capacity and cycle stability due to the addition of Mo2C / NC.

[0047] See also Fig.10 , the figure shows the rate performance test results of the lithium-sulfur battery in Example 1 and Comparative Example 1, which are charged and discharged at 0.1C, 0.2C, 0.5C, 1C and 2C respectively. The lithium-sulfur battery prepared in Example 1 has a discharge capacity of 1210.9mAh / g at a low rate of 0.1C, and a discharge capacity of 657.7mAh / g at a high rate of 2C. In contrast, the lithium-sulfur battery assembled in Comparative Example 1 has a discharge capacity of 901.5mAh / g at a low rate of 0.1C, and a discharge capacity of only 124.5mAh / g at a high rate of 2C, indicating that the rate performance of the lithium-sulfur battery in Comparative Example 1 is significantly lower than that of Example 1.

[0048] The above battery performance test results show that when the molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC) provided by the present invention is used as a functional additive for the positive electrode of a lithium-sulfur battery, the electrochemical performance of the lithium-sulfur battery is significantly improved, mainly due to: nitrogen-doped carbon has a hierarchical porous structure, which enhances the electrolyte penetration and ion transmission capacity; nitrogen-doped active sites not only enhance the adsorption performance of porous carbon to polysulfides, but also can improve its catalytic activity by optimizing the coordination structure of Mo2C; Mo2C can chemically adsorb and efficiently catalyze the reversible transformation of polysulfides, thereby improving the utilization rate of active substances. The composite material is used as a functional additive for the positive electrode of a lithium-sulfur battery, which can effectively inhibit the dissolution and shuttle of polysulfides, and significantly improve the capacity, rate performance and cycle stability of the battery.

[0049] Example 2

[0050] The preparation method of this embodiment is the same as that of embodiment 1, except that glucose (C6H 12O6) is adjusted to 0.7g, and other conditions remain unchanged. Compared with the Mo2C / NC composite material prepared in Example 1, the content of the carbon source is increased in this embodiment, resulting in a decrease in the specific surface area of ​​the prepared Mo2C / NC composite material, which is not conducive to the construction of a stable porous interconnected structure, reduces the infiltration and penetration of the electrolyte into the active material, and reduces the electrochemical reaction kinetics. The electrochemical properties such as capacity and cycle stability of the lithium-sulfur battery assembled in this embodiment are reduced compared with those in Example 1: the initial discharge capacity at 0.5C is 704.4mAh / g, the capacity after 500 cycles is 357.2mAh / g, and the capacity retention rate is 50.71%.

[0051] Example 3

[0052] The preparation method of this embodiment is the same as that of Example 1, except that the amount of ammonium molybdate ((NH4)2MoO4·4H2O) in step (2) is adjusted to 0.08 g, and other conditions remain unchanged. Compared with the Mo2C / NC composite material prepared in Example 1, the content of the molybdenum source is reduced in this embodiment, resulting in a lower Mo2C content in the prepared Mo2C / NC composite material. The electrochemical properties such as capacity and cycle stability of the lithium-sulfur battery assembled in this embodiment are reduced compared with those in Example 1: the initial discharge capacity at 0.5C is 824.4 mAh / g, the capacity after 500 cycles is 271.2 mAh / g, and the capacity retention rate is 32.9%.

[0053] Example 4

[0054] The preparation method of this embodiment is the same as that of Example 1, except that the high-temperature calcination time in step (4) is reduced to 1 h, and other conditions remain unchanged. Compared with Example 1, the high-temperature calcination time of the Mo2C / NC composite material in this embodiment is reduced, resulting in a lower content of the active substance Mo2C in the Mo2C / NC composite material, and a significant decrease in electrochemical performance. The electrochemical properties such as capacity and cycle stability of the lithium-sulfur battery assembled in this embodiment are reduced compared with those in Example 1: the initial discharge capacity at 0.5C is 724.4 mAh / g, the capacity after 500 cycles is 327.2 mAh / g, and the capacity retention rate is 45.2%.

[0055] The above contents are merely examples and explanations of the concept of the present invention. Various modifications or supplements made to the described specific embodiments or replacements made by technicians in the technical field in a similar manner shall fall within the protection scope of the present invention as long as they do not deviate from the concept of the invention or exceed the scope defined by the claims.

Claims

1. A molybdenum carbide / nitrogen-doped carbon composite material, characterized in that: Fine Mo2C nanoparticles are uniformly dispersed in the nitrogen-doped carbon matrix.

2. A method for preparing the molybdenum carbide / nitrogen-doped carbon composite material as claimed in claim 1, characterized in that: g-C3N4 was used as template, ammonium molybdate ((NH4)2MoO4·4H2O) as molybdenum source, glucose (C6H 12 O6) as a carbon source, which are uniformly mixed and then hydrothermally and high-temperature calcined to obtain a molybdenum carbide / nitrogen-doped carbon composite material (Mo2C / NC).

3. The preparation method according to claim 2, characterized in that: The specific steps are as follows: (1) placing 20-25 g of urea in a tubular furnace for high-temperature calcination to obtain g-C3N4, wherein the calcination atmosphere is air, the temperature is 520-560°C, the holding time is 3-4 h, and the heating rate is 3-5°C / min; (2) At room temperature, 0.1-0.2 g (NH4)2MoO4·4H2O and 0.4-0.6 g C6H 12 O6 was dissolved in 20 mL of deionized water, and 0.1-0.2 g of g-C3N4 was ultrasonically dispersed in the solution and stirred for 8-12 h to obtain a milky white solution; (3) placing the mixed solution obtained in step (2) in a reaction vessel for hydrothermal reaction at a temperature of 120 to 150° C. for 8 to 12 hours; then filtering the reaction product and drying it for later use; (4) placing the product obtained in step (3) in an inert atmosphere for high-temperature calcination treatment, wherein the calcination atmosphere is argon, the temperature is 800-850° C., the holding time is 2-3 h, and the heating rate is 2-4° C. / min, to obtain Mo2C / NC; (5) The Mo2C / NC prepared in step (4) is fully ground and mixed with Ketjen black (KB) in a certain proportion to obtain a conductive carrier (KB / Mo2C / NC), wherein the mass ratio of Mo2C / NC is 2% to 8%; the conductive carrier is composited with active sulfur by a melt sulfurization process to obtain a composite sulfur positive electrode material (KB / Mo2C / NC-S) for a lithium-sulfur battery.

4. The use of the molybdenum carbide / nitrogen-doped carbon composite material in a lithium-sulfur battery positive electrode material as claimed in claim 1, characterized in that: A composite sulfur positive electrode material (KB / Mo2C / NC-S) for a lithium-sulfur battery prepared using a molybdenum carbide / nitrogen-doped carbon composite material, a conductive agent, and a binder are fully ground and mixed in a mass ratio of 8:1:1 to obtain a slurry; the obtained slurry is evenly coated on an aluminum foil, vacuum dried at 70°C for 24 hours and cut to obtain a lithium-sulfur battery positive electrode sheet, wherein the molybdenum carbide / nitrogen-doped carbon composite material, as a functional additive for a lithium-sulfur battery positive electrode, can effectively improve the utilization rate of active sulfur.

5. The use according to claim 4, characterized in that The active sulfur area loading in the prepared lithium-sulfur battery cathode is 1.5-2.0 mg / cm 2 .

Citation Information

Patent Citations

  • Preparation method of carbon nanotube-loaded molybdenum carbide material and application of molybdenum carbide material in positive electrode material of lithium-sulfur battery

    CN107425185A

  • Nitrogen-doped carbon nanotube coated metal nickel / molybdenum carbide composite electrocatalyst and preparation method and application thereof

    CN111530492A

  • Positive electrode carrier of lithium-sulfur battery as well as preparation method and application of positive electrode carrier

    CN114335555A

  • Preparation method of nitrogen-doped carbon shell coated molybdenum carbide core microsphere material with core-shell structure

    CN114560463A

  • Lithium-sulfur battery positive electrode material and preparation method thereof

    CN115732662A

Cited By

  • Modified PE diaphragm with low decomposition voltage and high lithium supplement capacity and preparation method thereof

    CN121355518A

  • Sodium ferric phosphate pyrophosphate positive electrode material, preparation method thereof and electrochemical device

    CN121672460A